Implementasi Kebijakan Penetapan Ruang Lingkup Penanganan Prasarana dan Sarana Umum Tingkat Kelurahan dalam Upaya Meningkatkan Kinerja Petugas Penanganan Sarana Umum di Kecamatan Cempaka Putih - Dina Evirinindya; Dian Wahyudin (Reformasi Administrasi, 2025)
Recently, satisfaction with the performance of PPSU officers tends to decline in Cempaka Putih sub-district, therefore mapping the Technical Guidelines for Handling Public Infrastructure and Facilities at the Village Level in accordance with Governor's Decree Number 280 of 2023 is expected to improve the performance of PPSU officers. The purpose of this study is to analyze and evaluate the Implementation of the Policy for Determining the Scope of Handling Public Infrastructure and Facilities at the Village Level in an Effort to Improve the Performance of Public Facility Handling Officers in Cempaka Putih Sub-district. The research approach is qualitative descriptive. The conclusion of this study is that the Implementation of the Policy for Determining the Scope of Handling Public Infrastructure and Facilities at the Village Level has not gone well so that it has not been able to improve the performance of Public Facility Handling Officers in Cempaka Putih Sub-district even though the policy has been implemented and has various aspects of description, implementation steps, scope of handling public infrastructure and facilities. This deficiency is caused because the community environment has not fully supported the implementation of the policy due to the lack of understanding of some people which causes PPSU officers to be unable to handle public facilities and infrastructure in accordance with the scope of the policy that has been determined, in addition, several PPSU officers are still found who do not carry out their duties properly due to lack of motivation and sense of responsibility even though the recruitment process for the PPSU selection team in the sub-district has been very thorough and strict to find officers with the appropriate competencies in their fields.